ChemInform Abstract: New Research Areas Inspired by Sustainable Development. Issue 31 (11th July 2013) - Da Silva, Eric; Dayoub, Wissam; Duguet, Nicolas; Metay, Estelle; Popowycz, Florence; Lemaire, Marc
Abstract Review: 73 refs.